Gestión del control interno de las cuentas por cobrar en el Gobierno Autónomo Descentralizado Municipal del Cantón Baba, periodo 2020 - 2021. - Álava Manzo, Jamilex Anais (2022)
In this case study, an analysis of the internal control management of accounts receivable of the GAD Municipal del Canton Baba from 2020 to 2021, an entity that is accountable to the state for the public resources that are within its territory and that performs executive and legislative functions of central, regional and local bodies and agencies governed by COOTAD was conducted. To carry out this case, a set of investigative methods such as interviews, direct observations and analysis of financial documents were used to determine the shortcomings in the management of internal control of accounts receivable and their impact on the entity's economic performance. Internal control is fundamental for this and other public sector entities since it is the key to maintain the operation and economic welfare of the same, it also allows measuring the effectiveness and efficiency of its administrative, accounting or financial processes, so the entity must take measures focused on the management of internal control of existing accounts receivable, and in turn allows it to achieve an adequate administration that avoids future financial losses.